Religiousness in the Late Middle Ages - Bylina, Stanisław (2019)
This book is devoted to the religiosity of the medieval Christian masses in Central and Eastern Europe and its relationship with the traditional cultures of that time. Addressing such topics as the common instruction of the three prayers and the Decalogue, "Christian" magic in everyday life, the Marian devotion, and various images of heaven and eternal damnation, the author never loses sight of his main topic: the complex and powerful interaction between medieval folklore and Christianity.